Meme : poems - Wheeler, Susan, 1955- (Kuhl House poets, 2012)
Acclaimed poet Susan Wheeler, whose last individual collection predicted the spiritual losses of the economic collapse, turns her attention to the most intimate of subjects: the absence or loss of love. A meme is a unit of thought replicated by imitation; examples of memes, Richard Dawkins wrote, "are tunes, ideas, catch-phrases, clothes fashions, ways of making pots or of building arches." Occupy Wall Street is a meme, as are internet ideas and images that go viral. What could be more potent memes than those passed down by parents to their children?